Negotiating feminine identities and condom use scripts amongst heterosexual women in Singapore - Shrutika Ajit Mangharam (2015)
Since the contraceptive revolution in the 1960s, condoms have emerged as one of the most commonly used methods of contraception. This paper utilises gender schema theory and sexual scripts associated with gender identity to assess the relationship between women’s feminine identities and their condom use habits. By analysing the interview responses of heterosexual women in Singapore, the study also highlights the influence of social stigma on women’s condom use habits. Previous literature on gender identity and condom use indicates that women who accept traditional feminine identities also adhere to traditional condom use scripts. While the findings of the current study confirm this, they also highlight that women sometimes choose to redefine femininity and deviate from traditional condom use scripts. The paper also explores how some women, despite rejecting traditional femininity, continue to adhere to traditional condom use scripts to avoid being stigmatised.